New trends of cloud kitchen technology and consumers’ purchase decisions: a conceptual study / Nurul Syahirah Idris, Muhammad Afiq Aiman Zulkifly and Dr. Muhammad Safuan Abdul Latip - Idris, Nurul Syahirah; Zulkifly, Muhammad Afiq Aiman; Abdul Latip, Muhammad Safuan (Universiti Teknologi MARA, Kedah, 2023)
This conceptual paper aims to explore the potential research area of Cloud Kitchens and their impact on consumer purchase decisions. With the ever-increasing demand for food delivery, Cloud Kitchens have emerged as a viable alternative to traditional restaurant models. Operating without a physical location or dining area, they present unique challenges and opportunities for stakeholders in the food industry. By identifying potential predictors of Cloud Kitchen purchase decisions through a literature review, this study can contribute to promoting and ensuring the quality of Cloud Kitchen products and services in the future. The findings of this study can benefit all stakeholders, including Cloud Kitchen operators, consumers, and policymakers, by providing insights into the key factors influencing consumer purchase decisions. This paper highlights the need for further research in this area and contributes to the existing literature on Cloud Kitchens and their impact on the food industry.